THE IMPACT OF INTERIOR DESIGN ELDERLY CARE FUNCTIONAL SUPPORT IN OLD HOMES FOR THE ELDERLY’S QUALITY OF LIFE - Huiling, Liu; Hye, A. K. Mahbubul (Asia Pacific Journal of Religions and Cultures, 2023)
The purpose of this study is to explore the decision of elderly care function planning in the interior design of Old People’s Home and examine the support framework of interior design to improve the quality of life of the elderly and try to positively affect the quality of life of the elderly. In this study, based on the comprehensive interior design support theory for elderly care functions, combined with previous studies on the relationship between living environment or elderly care service supply and the quality of life of the elderly, this study conducted a questionnaire survey on 461 elderly people in Taiyuan City, Shanxi Province, China by using qualitative analysis. SPSS was used to analyze the data obtained from the questionnaire statistically. The functional factors of interior design for the elderly that had a significant impact on the quality of life of the elderly were identified. The hypothesis and impact model was verified by structural modeling (SEM). The results of the study show that the supporting factors of elderly care functions in interior design have a positive impact on the quality of life of the elderly. In addition, the educational background and family status of the elderly play a moderating role. This paper discusses the enlightenment of these research results to the research on the optimization of elderly care functions in the interior design of elderly care institutions and the practice of interior design.